Single-Visit Pulp Revascularization of a Nonvital Immature Permanent Tooth Using Biodentine - Aldakak, Mohammad Mhd nader; Capar, Ismail Davut; Rekab, Mohammad Salem; Abboud, Souad (Iranian Endodontic Journal, 2016)
An 11-year-old female patient was referred with a chief complaint of pain in the right mandibular second premolar. Clinical and radiographic examinations showed secondary caries under an old composite restoration, a negative response to a pulp test and an immature root with an open apex. After root canal cleaning and shaping, bleeding was invoked in the canal up to 2 mm short of the cemento-enamel junction (CEJ). After 10 min to allow clotting at this level, a plug of Biodentine was placed over the blood clot and the tooth was temporized with glass ionomer cement. At the next visit, the tooth was free of symptoms and a permanent filling was placed. Clinical and radiographic examinations during a two-year follow-up showed complete root maturation and intact supporting soft tissues without sinus tract, pain or swelling. Conclusion: The use of Biodentine in a single-visit apexification protocol to treat an immature permanent tooth with necrotic pulp can create a suitable environment for revascularization, resulting in the completion of root maturation. Key Words:Biodentine; Immature Apex; Pulp Revascularization